2008
DOI: 10.1002/mrm.21626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feature extraction for brain tumor classification based on short echo time 1H MR spectra

Abstract: This study examines the effect of feature extraction methods prior to automated pattern recognition based on magnetic resonance spectroscopy (MRS) for brain tumor diagnosis. Since individual inspection of spectra is time-consuming and requires specific spectroscopic expertise, the introduction of clinical decision support systems (DSSs) is expected to strongly promote the clinical use of MRS. This study focuses on the feature extraction step in the preprocessing protocol of MRS when using a DSS. On two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…Classifiers were designed and evaluated using features from Short-TE and Long-TE alone and a combination of both TEs, ShortTE+Long-TE. Our results were compared with those in previous studies [27][28][29][30].Based on the results of previous studies [15,20,26,29 …”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Classifiers were designed and evaluated using features from Short-TE and Long-TE alone and a combination of both TEs, ShortTE+Long-TE. Our results were compared with those in previous studies [27][28][29][30].Based on the results of previous studies [15,20,26,29 …”
mentioning
confidence: 74%
“…PI automatically estimates with proportionality to the concentration of 11 main metabolites for Short-TE and 8 metabolites for Long-TE MRS [15,26]. Details of these estimations are given in the Supplementary…”
Section: Mrs Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously to the PR methods selected for classification, PCA has been widely accepted in the literature and is a simple, standard and straigh multivariate technique that obtains reasonably good results in MRS feature extraction [83,84].…”
Section: Feature Extraction With Multivariate Statistical Analysismentioning
confidence: 99%
“…They reported that PR methods perform at least as well as the ones based on manual quantitation obtaining 5%-10% higher accuracy when automatic techniques were applied. Classifiers for in vivo Short-TE spectra and Further investigation with LS-SVM and feature extraction methods for MRS was carried out by Luts et al [84] during a subsequent EC project called eTUMOUR. Luts et al studied the effect of automating the feature extraction step in the preprocessing protocol of Short-TE spectra.…”
Section: Survey Of Studies Performed With Mrs Data From Adultsmentioning
confidence: 99%